2004
DOI: 10.1142/s0219455404001148
|View full text |Cite
|
Sign up to set email alerts
|

Shear Buckling of Corrugated Plates With Edges Elastically Restrained Against Rotation

Abstract: This paper presents an estimation of the elastic shear buckling capacity of corrugated plates with edges elastically restrained against rotation. The corrugated plate possesses higher shear buckling capacity compared to an unfolded flat plate. It has been used to replace the concrete web in PC box girders in recent bridge constructions in Japan. In this study, the corrugated plate is modelled as an orthotropic Mindlin plate. Elastically rotational restraint on boundary edges is taken into account in the form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…This is not necessarily because approximated solutions are enough for engineering applications. A simple and valid approximated analysis for corrugated plates can be conducted by analysing them as orthotropic plates [1][2][3][4][5][6][7][8][9][10][11][12] of uniform thickness and equivalent rigidities (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not necessarily because approximated solutions are enough for engineering applications. A simple and valid approximated analysis for corrugated plates can be conducted by analysing them as orthotropic plates [1][2][3][4][5][6][7][8][9][10][11][12] of uniform thickness and equivalent rigidities (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Following the same approach as Briassoulis [7], Samanta et al [10] derived new expressions for the equivalent extensional rigidity of trapezoidally corrugated plates, and carried out free vibration and geometric nonlinear analyses of such plates with the new expressions. Semenyuk et al [11] and Machimdamrong et al [12] considered the transverse shear stresses of thick corrugated plates and derived the equivalent expression of transverse shear modulus for them. After studying the computation results for a series of corrugated shells, Semenyuk et al [11] also found the limitations of the equivalent expressions and presented the conditions under which a corrugated shell should not be treated as an orthotropic circular shell.…”
Section: Introductionmentioning
confidence: 99%
“…The scope of the damage plasticity model ABAQUS: it provides the damage plasticity model suitable for the following finite element analysis [7]:…”
Section: Simulation Of Materials Nonlinearity Of Concrete Using Damagementioning
confidence: 99%
“…2πr dr (11) in which ρ is the mass density of the plate material. The governing equations are derived from a variational procedure, the extended Hamilton's principle for the nonconservative system is used.…”
Section: Dynamic Governing Equationsmentioning
confidence: 99%
“…Review of the literature indicates that the researchers have given a great attention to the nonlinear problems in a corrugated circular plate, analytically and numerically, based on two nonlinear bending theories: isotropic shallow shell theory [3,4] and anisotropic plane plate theory [5,6]. These efforts have covered various aspects of the nonlinear problem with regard to a corrugated plate, including the vibration [7,8], bending [9,10], and stability [11]. Generally, the nonlinear bending theory of plates based approach is applicable to corrugated circular plate with dense corrugations of various types, while the shells based way proves to be independent of the density of corrugations [4,12].…”
Section: Introductionmentioning
confidence: 99%